THE SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF COMMUNICATION IN THE STUDENT COMMUNITY - Karakulovich, Juraev Atham (Journal of Geography, Regional Planning and Development, 2025)
Objective: This study aims to analyze the socio-psychological characteristics of communication within the student community, focusing on the dynamics that influence interpersonal interactions and their implications for academic and professional success. Method: A qualitative approach was employed, utilizing structured interviews and observational techniques to gather data from a diverse sample of university students across various academic disciplines. Thematic analysis was conducted to identify recurring patterns and significant factors in communication behaviors. Results: The findings reveal that communication effectiveness in the student community is significantly shaped by psychological traits such as empathy, self-esteem, and adaptability, alongside environmental factors like peer support and academic pressure. Barriers to communication were linked to social anxiety, lack of feedback, and cultural diversity. Moreover, students who developed adaptive communication strategies demonstrated higher levels of personal growth and academic achievement. Novelty: This research offers a comprehensive socio-psychological perspective on student communication, emphasizing the interrelation between communication skills and educational success. It contributes original insights by integrating personal development with communication theory, proposing targeted strategies to foster effective interpersonal communication in academic settings.